2002
DOI: 10.1159/000072351
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Ultrasonographic Measurements of Internal Jugular Veins in the Placement of Central Venous Catheters in ENT Cancer Patients

Abstract: Objective: To assess the possible differences between right and left internal jugular veins in head and neck cancer patients, in order to choose one of them for cannulation. Patients and Methods: A prospective study was designed including 102 internal jugular veins of 51 head and neck cancer patients evaluated by means of duplex Doppler ultrasonography. Patency, presence of thrombosis, characteristics of the vein wall, compressibility, area of vein both at rest and during Valsalva maneuver, expiratory flow spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…With respect to the quantitative Doppler parameters, PRIM et al (8) reported a high disparity of area, expiratory and jugular flow speed between right and left IJV for patients with head and neck cancer. But, no statistically significant differences were found between sides.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the quantitative Doppler parameters, PRIM et al (8) reported a high disparity of area, expiratory and jugular flow speed between right and left IJV for patients with head and neck cancer. But, no statistically significant differences were found between sides.…”
Section: Discussionmentioning
confidence: 99%